Community Service: Entrepreneurship And Cultural Collaboration To Improve The Quality Of University - Evi Mutia; Iskandarsyah Madjid; Noor Azuddin Yakob; Jhon Andra Asmara; Ratna Mulyany; Fazli Syam BZ; Farid Farid; Ade Irma Suryani; Halimatussakdiah Halimatussakdiah; Ahmad Nizam; Chenny Seftarita; Bambang Bambang (International Journal Of Community Service, 2023)
This community service carries the theme of entrepreneurship and cultural collaboration, which aims to improve the quality of universities. Universities act as centers of academic learning and as agents of positive transformation and foster an entrepreneurial mindset among their students. This activity was carried out by the Faculty of Economics and Business, Universitas Syiah Kuala, in collaboration with the Graduate School of Business, Universiti Kebangsaan Malaysia. Using Service Learning (SL) and Partnership/Collaboration methods, this program combines entrepreneurship and cultural collaboration, providing a holistic approach to university engagement. Entrepreneurship education has gained significant recognition as a catalyst for innovation, economic growth, and job creation. Cultural collaboration, in parallel, underscores the importance of preserving and celebrating cultural diversity while fostering cross-cultural understanding, which in this program is carried out by rebranding the university in particular and Aceh in general. As the university grows, its commitment to community service remains a cornerstone of its mission to create a better, more inclusive, and culturally enriched society. Future initiatives could explore deeper aspects, such as innovation and sustainable collaboration strategies.